What Makes the Swiss Banks Special? - Haciyeva, Salatin; Heyderova, Aybeniz (International Journal of Membrane Science and Technology, 2023)
The Swiss banking sector has long been famous for its success in attracting foreign assets and wealthy clients. This article aims to analyze the reasons behind the success of Swiss banks by considering various factors. The research paper includes a literature review, methodology, and examination of key elements such as foreign assets, Indian ’black money,’ the largest Swiss banks, the impact of the coronavirus crisis, Swiss banking secrecy, overall country stability, stable currency, and globalization. The study reveals that Swiss banks have historically been a preferred destination for people from politically and economically unstable countries seeking secure storage for their wealth. The existence of banking secrecy laws, dating back to 1930s, has played a significant role in attracting international clients, although other factors have also contributed to the success of the sector. The analysis of foreign assets shows a substantial amount of money held in Swiss banks, accounting for a significant portion of global cross-border assets. Indian ’black money’ has also found its way to Swiss banks, although efforts to disclose account information have been ongoing. The largest Swiss banks, including UBS and Credit Suisse, have played a pivotal role in the country’s financial sector. The impact of the coronavirus pandemic on the Swiss banking industry was analyzed, showing that despite challenges, the industry managed to offer new jobs and maintain profitability. The study emphasizes the importance of Swiss banking secrecy, which has been a key factor in attracting wealthy clients for centuries. However, it argues that secrecy alone does not fully explain the success of the Swiss banks. Other factors, such as overall country stability, a stable and easy convertible currency like the Swiss Franc, and the role of globalization in facilitating international operations, have all contributed to the sector’s prominence. In conclusion, the success of Swiss banks is a result of multiple factors working together. While banking secrecy has played a significant role, other favorable conditions such as political stability, a strong currency, and global outreach have also contributed to Switzerland’s status as a global financial hub. Understanding the interplay of these elements sheds light on the reasons behind the exceptional performance of the Swiss banking sector.